URBAN WATERSHED EUTROPHICATION STATE MONITORING USING AQUATIC PLANT-BASED GREEN TECHNOLOGY IN ISLAMIC BUILT ENVIRONMENT - Hanifah, Nurul Azlen; Othman, Rashidi (INSTITUT TERJEMAHAN & BUKU MALAYSIA BERHAD, 2016)
Nature and natural resources are precious gift to mankind. Regrettably, as day by day, the world is changing a bit by bit. The situations tend to be exaggerated and over exploitation natural resources have been anywhere. One of the major crisis now is eutrophication is not just; it has become a worldwide issue. Nitrogen and phosphorus are important elements that always correlate with eutrophication. Their excessive present in water bodies resulting over accumulation of green algae elevates production of aquatic plants, depletion of dissolved oxygen, diminishing the species diversity and affecting the whole aquatic ecosystem as a whole. Human activities are a major contribution to this issue. Phytotechnology is another alternative new method in landscape ecology to treat eutrophication and to prove that aquatic plants can be used as indicator to evaluate and monitor state of lake ecosystem as healthy or unhealthy environment. Hence, Islam teaches that Muslims have a responsibility to protect the environment, as stewards of the Earth that God created. We are not masters who rule over the earth but servants of God with a responsibility to maintain the balance which He has created.